2013
DOI: 10.1016/j.ijrobp.2013.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Toxicity Analysis of 3-Dimensional Conformal Radiation Therapy Versus Intensity Modulated Radiation Therapy on the High-Dose Arm of the Radiation Therapy Oncology Group 0126 Prostate Cancer Trial

Abstract: Purpose A Preliminary report of clinical and treatment factors associated with toxicity in men receiving high dose radiation (RT) on a phase III dose escalation trial. Methods and Materials Trial was initiated with 3 dimensional RT (3DCRT) and amended after 1 year to allow intensity modulated RT (IMRT). Patients treated with 3DCRT received 55.8Gy to a planning target volume that included the prostate and seminal vesicles then 23.4Gy to prostate only. IMRT patients were treated to the prostate and proximal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
206
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(217 citation statements)
references
References 28 publications
8
206
2
1
Order By: Relevance
“…The rate of patients free from G2 acute urinary, rectal and intestinal toxicities [25]. In the present study, the intermediate risk patients represented only 13% of the entire cohort with the remaining 87% being high risk.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The rate of patients free from G2 acute urinary, rectal and intestinal toxicities [25]. In the present study, the intermediate risk patients represented only 13% of the entire cohort with the remaining 87% being high risk.…”
Section: Discussionmentioning
confidence: 53%
“…This may be attributed to a larger treatment volume in the present study (by including the pelvic nodes in high risk cases) with subsequent higher bladder dose. Also, the use of fiducial markers in our study allows for a tighter posterior margin with subsequent sparing of the rectum [25].…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, acute (grade 2/3) genitourinary (GU) and gastrointestinal (GI) side effects have been reported in 30-50% of cases, and severe side effects, including chronic rectal bleeding ≥ grade 2, have been reported in 6-20% of patients. 4,5 Several studies analyzed the inter-and intrafractional displacements of the prostate, which ranged from 0.2 to 21 mm 6 depending on rectal and bladder filling. Our prospective analysis of 66 prostate cancer patients demonstrated that standardized prostate immobilization using an endorectal balloon significantly reduced organ motion.…”
Section: Introductionmentioning
confidence: 99%
“…In the management of localized prostate cancer, multiple treatment options have been employed, including radical prostatectomy, external beam radiation therapy using intensity‐modulated photon beam (IMRT), brachytherapy, cryotherapy, and proton therapy 1, 2, 3. Proton therapy provides an advantage over IMRT by reducing the radiation dose delivered to normal tissues outside of the target volume 4, 5.…”
Section: Introductionmentioning
confidence: 99%